Comparative Study of Phonological Systems of Turkic Languages - Madaliev, Yarmukhamed (The Lingua Spectrum, 2024)
This article explores the comparative study of phonological systems in Turkic languages, a critical area of linguistic research that reveals structural, historical, and typological patterns. The study investigates phoneme inventories, vowel harmony, consonant assimilation, and prosodic features within the family of Turkic languages. By leveraging comparative methods, the article identifies shared phonological features and points of divergence, shedding light on historical language development and the impact of contact with non-Turkic languages. The research highlights both theoretical insights and practical applications in linguistic typology, historical linguistics, and language teaching.